The impact of hospital accreditation in selected Middle East countries: a scoping review. Issue 1 (17th August 2021) - Khan, Salma; Yousefinezhadi, Taraneh; Hinchcliff, Reece
Abstract : Purpose: There is conflicting evidence concerning the impact of hospital accreditation programmes, including across the Middle East Region, where such programmes have been most recently implemented in Iran, Jordan and Saudi Arabia. This paper maps available evidence regarding the impact of hospital accreditation in these three countries and draws attention to knowledge gaps for consideration. Design/methodology/approach: This scoping review was conducted in 2020, using the Arksey and O'Malley framework. Five research databases were searched, along with five government and accreditation agency websites. Searches were complemented by citation chaining. English and Arabic publications evaluating hospital accreditation in the selected countries were included. Commentaries and articles not based on primary data collection and reviews of existing registry data were excluded. There were no exclusions based on study design or methods. A descriptive numerical summary and thematic analysis were used to synthesise the literature. Findings: studies were included. The majority ( n  = 35) were published since 2014 and conducted in Saudi Arabia ( n  = 16). Four themes emerged: organisational impacts, patient safety, quality of care, and patient satisfaction and experience. The literature generally highlights positive impacts of accreditation, but most studies were based solely on health professionals' subjective perceptions. "Organisational impacts" had the largest, and strongest body of supporting evidence, while "patient safety" had the least and most variable evidence. Originality/value: Opportunities to strengthen the design and evaluation of hospital accreditation programmes in the selected countries are highlighted. Additional experimental, mixed-method research is recommended to strengthen the evidence base and inform practical enhancements to hospital accreditation programmes in the region.